Assessment of Thyroid Disorder in FarWestern Part of Nepal: A Hospital Based Study - Yadav, Naval Kishor; hanpari, C; Shrewastwa, Mukesh Kumar; Mittal, Rabindra Kumar; Koner, Bidhan Chandra (Bangladesh Journal of Medical Science, 2012)
Objectives: This study was conducted to know the status of thyroid disorder in people of far western region of Nepal. Methods: A total of 808 cases, out of which 133 male and 675 female were included and study was carried out using data retrieved from the register maintained in the Department of Biochemistry of the Nepalgunj Teaching Hospital, Kohalpur, Banke, Nepal, between 1st January, 2011 and 28th February, 2012. The variables collected were age, sex, and thyroid function profile including free T3, free T4 and TSH. The data was analyzed using Excel 2003, R 2.8.0 Statistical Package for the Social Sciences (SPSS) for Windows Version 16.0 (SPSS Inc; Chicago, IL, USA) and the EPI Info 3.5.1 Windows Version. Results: The percentage of thyroid disorders was 33.66% in people of far western region of Nepal. The people were highly affected by overt hyperthyroidism (14.9%) followed by subclinical hyperthyroidism (9.9%). The subclinical hypothyroidism was 7.9% while 1% overt hypothyroidism only. Serum fT3, fT4 and TSH level were significantly different in male and females. Similarly, fT3, fT4 and TSH levels show statistically significant differences in different thyroid disorders. The fT3 and fT4 level in overt hyperthyroidism and subclinical hypothyroidism showed statistically significant differences when compared with euthyroidism group. Likewise, TSH level also shows statistically significant in all the thyroid disorders when compared with euthyroidism group. The fT3 and fT4 levels were statistically insignificant in all the age groups whereas TSH level showed statistically significant different in all the age groups. The fT3 and fT4 level in 21-40 years showed statistically significant when compared with serum level of fT3 and fT4 of 0-20 years. Similarly, serum level of TSH in 21-40 and 41-60 years also showed statistically significant when compared with serum level of TSH of 0-20 years. Conclusion: The people residing in far western region have risk for thyroid disorders. They were suffering with thyroid disorder, especially overt hyperthyroidism (14.9%) and subclinical hyperthyroidism (9.9%). Further studies are required to characterize the reasons for this high prevalence of overt hyperthyroidism and subclinical hyperthyroidism. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12601 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12